2016
DOI: 10.22159/ijpps.2016v8i10.5005
|View full text |Cite
|
Sign up to set email alerts
|

Mini Review on Therapeutic Profile of Phenoxy Acids and Thier Derivatives

Abstract: <p>Phenoxy acids and their derivatives are associated with a variety of biological activities such as antihyperlipidemic, hypoglycemic, antimicrobial, antiviral, antitubercular, anti-inflammatory, analgesic, antioxidant, anticancer and antihypertensive activities. This mini review outlines diverse biological properties of phenoxy acids and their derivatives. </p>

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Phenoxy acids are unquestionably among the most significant functional groups in organic chemistry. They are present, among several other structures, in certain naturally occurring particles, synthesized polymers, peptides, and pharmaceutical agents [4][5][6][7]. The formation of phenoxy acid bonds was one of the most significant pharmaceutical synthesis transformations [8,9], taking into account a high percentage of all preliminary evaluation responses in industrial and medical applications laboratories as recently reported [10].…”
Section: Introductionmentioning
confidence: 92%
“…Phenoxy acids are unquestionably among the most significant functional groups in organic chemistry. They are present, among several other structures, in certain naturally occurring particles, synthesized polymers, peptides, and pharmaceutical agents [4][5][6][7]. The formation of phenoxy acid bonds was one of the most significant pharmaceutical synthesis transformations [8,9], taking into account a high percentage of all preliminary evaluation responses in industrial and medical applications laboratories as recently reported [10].…”
Section: Introductionmentioning
confidence: 92%
“…Phenoxy acetic acid is an organic compound that represents a group of phenoxy acetic acid derivatives containing anisole in which acetic acid or its derivatives are linked to the methane group Fig. 1 [ 40 ]. Phenoxy acetic acid is often known to be monocarboxylic acid, which is the glycolic acid O -phenyl derivative with a sweet and sour tasting with significant smells like honey and can be found in cocoa and its products.…”
Section: An Overview Of Phenoxy Derivatives As Possible Therapeutic Cmentioning
confidence: 99%
“…The results showed that these compounds have effective biological activity against organisms such as Enterococcus faecile, Salmonella typhi, and Escherichia coli. 40 Soraya Sepehrfar et al studied new Schiff base 2-amino 2-methyl-1-propanol derivate complexes and investigated by Hirshfeld surface analysis and molecular simulation against SARS-CoV-2. 41 Considering the importance of the synthesis of new compounds with new biological properties in the development of biological drugs, we have focused on the synthesis and properties of new compounds.…”
Section: Introductionmentioning
confidence: 99%